现代汉语提问言语行为研究 ——兼与越南语对比 - Hoàng, Thanh Hương (Đại học ngoại ngữ, 2017)
The results of previous research show that, although there are a few researchers have studied Asking Speech Acts from pragmatics perspective, but most of them still exist different deficiencies. This thesis has been drawing the previous researching results that related to this study in order to discussing and revealling the characteristics of Asking Speech Acts in modern Chinese. During the study, this thesis has used pragmatics theory such as the theory of speech act, conversation analysis, context etc.